2021
DOI: 10.1038/s41467-021-25198-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic approach to the catalytic enantioselective synthesis of tetracyclic isochroman

Abstract: Polyketide oligomers containing the structure of tetracyclic isochroman comprise a large class of natural products with diverse activity. However, a general and stereoselective method towards the rapid construction of this structure remains challenging due to the inherent instability and complex stereochemistry of polyketide. By mimicking the biosynthetic pathway of this structurally diverse set of natural products, we herein develop an asymmetric hetero-Diels–Alder reaction of in-situ generated isochromene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
9
0
1
Order By: Relevance
“…In 2021, a Au(I)/Sc(III) bimetallic catalytic strategy utilizing in-situ generated isochromene and o-QM via an asymmetric hetero-Diels-Alder reaction was described by Li, Liu and coworkers to access the tetracyclic ring systems. [52] Inspired by Feng's works [53] and the results of control experiments as well as the absolute configuration of product, a possible mechanism was shown in Scheme face of o-QM is strongly shielded by the neighboring tert-butyl group. Therefore, the enol attacked o-QM from the Si face (TS-18) to construct the corresponding chiral carbon.…”
Section: Benzopyran-fused Polycyclic Acetalsmentioning
confidence: 98%
See 1 more Smart Citation
“…In 2021, a Au(I)/Sc(III) bimetallic catalytic strategy utilizing in-situ generated isochromene and o-QM via an asymmetric hetero-Diels-Alder reaction was described by Li, Liu and coworkers to access the tetracyclic ring systems. [52] Inspired by Feng's works [53] and the results of control experiments as well as the absolute configuration of product, a possible mechanism was shown in Scheme face of o-QM is strongly shielded by the neighboring tert-butyl group. Therefore, the enol attacked o-QM from the Si face (TS-18) to construct the corresponding chiral carbon.…”
Section: Benzopyran-fused Polycyclic Acetalsmentioning
confidence: 98%
“…Bimetallic relay catalysis has emerged as an efficient strategy for the synthesis of diverse skeletons incorporating biologically relevant structural motifs. In 2021, a Au(I)/Sc(III) bimetallic catalytic strategy utilizing in‐situ generated isochromene and o ‐QM via an asymmetric hetero‐Diels–Alder reaction was described by Li, Liu and coworkers to access the tetracyclic ring systems [52] . Inspired by Feng's works [53] and the results of control experiments as well as the absolute configuration of product, a possible mechanism was shown in Scheme 32.…”
Section: Benzopyran‐fused Polycyclic Acetalsmentioning
confidence: 99%
“…手性四环异色满骨架是许多具有重要生物活性的 天然产物的核心结构, 但是构建该类骨架并控制其多个 手性中心的立体选择性是一项非常具有挑战性的工作. 为了实现该目标, 2021 年, 李灿、刘龑及合作者 [27] 受到 生物催化的启发, 发展了原位产生的 o-QMs 与异色烯 的催化不对称反电子需求的氧杂 Diels-Alder 反应 (Scheme 19). 作者以邻羟基苄醇 6 作为 o-QMs 中间体 A 的前体, 以 2-炔丙基苯甲醇 45 作为异色烯中间体 G 的 前体, 利用 Au(I)/手性 Sc(III)双金属催化模式 [28] , 通过 仿生合成策略, 高对映选择性地合成了二十余个手性四 手性螺环杂环化合物广泛存在于众多天然产物和 生物活性分子中, 此类骨架的催化不对称构建一直是一 个研究热点 [29] .…”
Section: 邻羟基苄醇与活泼亚甲基类化合物的催化不 对称[4+2]环加成反应unclassified
“…In 2021, the research group of Liu and Li reported the first asymmetric hetero-Diels–Alder (HDA) reaction of 2-(hydroxylmethyl) phenol 12a and α-propargyl benzyl alcohol 12b by using a Au( i )/Sc( iii ) bimetallic catalytic system to afford the enantioenriched isochroman 12c (Scheme 12). 25 In order to investigate the reaction mechanism, the authors performed the reaction of isochromene 12d with 12a in the presence of Sc(OTf) 3 / L10 which gave the desired product 12c in good enantiomeric excess implying that the role of gold catalysts would be to generate the key intermediate isochromene 12d . On the basis of carbon isotope effect ( R / R 0 ) studies, the authors proposed that the [4+2] cycloaddition reaction of isochromene 12d with ortho -quinonemethide ( o -QM) follows a stepwise pathway.…”
Section: Gold-based Enantioselective Bimetallic Catalysismentioning
confidence: 99%